Child support and educational outcomes: Evidence from the British household panel survey - Ian Walker; Yu Zhu (University of Kent, Department of Economics, 2008)
There is some evidence to support the view that Child Support (CS), despite low compliance rates and a strong interaction with the welfare system, has played a positive role in reducing child poverty among non-intact families. However, relatively little research has addressed the role of CS on outcomes for the children concerned. There are good reasons for thinking that CS could leverage better outcomes than other forms of income support and, using a sample of dependent children in non-intact families from the British Household Panel Survey (BHPS), we find that CS received has an effect which is at least 10 times as large as that associated with variations in other sources of total household net income for two key educational outcomes: namely school leaving at the age of 16, and attaining 5 or more good GCSEs. We show that this remarkable and strong result is robust and, in particular, can be given a causal interpretation.
Keywords: D13; D31; J12; J13; J22; 330; parental separation; parental incomes; child support; educational outcomes; Familie; Niedrigeinkommen; Sozialhilfe; Familienleistungsausgleich; Kinder; Bildungsertrag; Großbritannien